TOXOPLASMOSIS DALAM KEHAMILAN - Abdullah Hamdan (Intisari Sains Medis, 2015)
Toxoplasmosis is caused by protozoa Toxoplasma gondii. In adults, the infectionis usually asymptomatic andwithout certain clinical manifestations. The active infection is most often encounterd in the newborn, whoacquired their infection in utero. Pregnant woman with toxoplasmosis may have an abortion, intra unterine fetaldeath, and if the infant survives the active infection hes is likely to be handicapped by serious residual centralnervous system and ocular lesions that can cause mental retardation. Therefore,pregnant woman must beprevented from toxoplasma infection, or cure as early as possible.